2021
DOI: 10.1108/jrim-03-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Consumer brand engagement on social media in the COVID-19 pandemic: the roles of country-of-origin and consumer animosity

Abstract: PurposeThe coronavirus disease (COVID-19) pandemic unprecedentedly shocks the market. Little is known about the impact of COVID-19 on brand engagement across country-of-origin (COO) and country-of-market (COM). To address the gap, this study examines how the spread of the COVID-19 affects consumer brand engagement on social media for global brands through the mechanisms of the COO and consumer animosity.Design/methodology/approachThe authors collect consumer engagement activity data from Facebook for eight glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
13
0
1
Order By: Relevance
“…Because the first case of Covid-19 was detected in China, the pandemic unleashed stigmatization and pandemic hate, especially against the East Asian and Chinese diaspora ( Ng, 2020 , Wang et al, 2021 ), which turned into pandemic animosity across nations worldwide ( Nawaz et al, 2020 ). Xenophobia, racism, and prejudice in the form of hostility, suspicion, and fear towards Chinese people and people arriving from China were recorded in multiple countries ( CGTN, 2020 , Halepas and Ferneini, 2020 , Jakovljevic et al, 2020 , Nawaz et al, 2020 , Ng, 2020 , Wang et al, 2021 ). Similarly, the Omicron variant, first detected in Botswana, triggered animosity towards South Africa after the country announced a surge of cases ( Mueller & Walsh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the first case of Covid-19 was detected in China, the pandemic unleashed stigmatization and pandemic hate, especially against the East Asian and Chinese diaspora ( Ng, 2020 , Wang et al, 2021 ), which turned into pandemic animosity across nations worldwide ( Nawaz et al, 2020 ). Xenophobia, racism, and prejudice in the form of hostility, suspicion, and fear towards Chinese people and people arriving from China were recorded in multiple countries ( CGTN, 2020 , Halepas and Ferneini, 2020 , Jakovljevic et al, 2020 , Nawaz et al, 2020 , Ng, 2020 , Wang et al, 2021 ). Similarly, the Omicron variant, first detected in Botswana, triggered animosity towards South Africa after the country announced a surge of cases ( Mueller & Walsh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed how the lack of trust in the quality of Chinese goods creates negative thoughts in consumers, and this is how Chinese goods come to be boycotted. 26 , 56 , 72 Another hypothesis was on the effect of the country of origin of the vaccine on the intention to recommend. The country of origin has a direct impact on the quality perception of the countries and consumers tend to buy and recommend new products by relying on the quality of the country without doing much research, which supports our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they found that the image of the country of origin for German and Chinese vaccines was a variable associated with the intention to be vaccinated. Wang et al 26 studied the country of origin and consumer hostility during the pandemic and revealed that with the increase in cases, brand loyalty decreased, and consumer hostility had a mediating role. Elarbah and Shebli 27 investigated the effect of the country of origin and product quality on product selection, while İzmir 28 investigated the effect of the country of origin on purchasing decisions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The COVID-19 emergency has disrupted markets and marketing locally, regionally, and globally (Sheth, 2022) and has affected consumer country-of-origin perceptions and consumer animosity (Wang et al, 2022b). National protectionism and antiglobalization sentiment have thus resurfaced (Mandler et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 emergency has disrupted markets and marketing locally, regionally, and globally (Sheth, 2022) and has affected consumer country-of-origin perceptions and consumer animosity (Wang et al. , 2022b).…”
Section: Introductionmentioning
confidence: 99%